Castrum Corcagiensis - Roman Experimental Archaeology in Ireland - Martin McAree (EXARC Journal)
Barrack blocks were a central feature in any Roman fort and functioned as the living spaces for a Century and its officers. While Roman forts varied in size from just over an acre for a simple ‘numerius’ fort, to over 55 acers for some large ‘legionary’ forts such as Deva (Chester), the layout of a barrack block was the same. Castrum Corcagiensis is an experimental archaeology project undertaken by Legion Ireland, the Roman Military Society of Ireland. The aim of the project is to reproduce a working Roman fort barrack block, similar to 1st century barracks found at Isca Silurum (Caerleon) and Deva (Chester), and function as a working Iron Age Roman military environment for re-enactment and experimental archaeology.